2014
DOI: 10.3109/02713683.2014.898774
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Cataract – The Role of Estrogen

Abstract: There is evidence from epidemiologic data that cataract is more common in women than men. This is not solely due to a higher rate of cataract extraction in women, as is the case in the western world, but several population-based studies show that females have a higher prevalence of lens opacities, especially cortical. There is no firm evidence that lifestyle-related factors are the cause of this gender discrepancy. Focus has therefore been directed towards the role of estrogen in cataract formation. Although d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 144 publications
7
85
2
8
Order By: Relevance
“…However, it has been hypothesized that albumin/total protein and serum triglyceride levels in women and postmenopausal estrogen deficiency 49 may be a factor associated with greater predisposition to nuclear cataract. 48 Previous study found an association between the incidence of PSC and higher BMI. 25 Although we did not find any significant association with either BMI/obesity or other phenotypic profiles, our observation that progression of NO is associated with higher cholesterol levels may be associated indirectly with the BMI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it has been hypothesized that albumin/total protein and serum triglyceride levels in women and postmenopausal estrogen deficiency 49 may be a factor associated with greater predisposition to nuclear cataract. 48 Previous study found an association between the incidence of PSC and higher BMI. 25 Although we did not find any significant association with either BMI/obesity or other phenotypic profiles, our observation that progression of NO is associated with higher cholesterol levels may be associated indirectly with the BMI.…”
Section: Discussionmentioning
confidence: 94%
“…30 Other cross-sectional studies report that women are at a greater risk for nuclear opacities. [44][45][46][47][48] The reason for this finding is not fully understood. However, it has been hypothesized that albumin/total protein and serum triglyceride levels in women and postmenopausal estrogen deficiency 49 may be a factor associated with greater predisposition to nuclear cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen may exert a protective effect against the oxidative stress that is important in cataractogenesis (5) . In the present study, TOS increased and TAC decreased in the crystalline lens of rats following menopause induction.…”
Section: Discussionmentioning
confidence: 99%
“…Some well-known systemic conditions such as diabetes mellitus (DM) and systemic steroid intake promote cataract formation (1)(2)(3)(4) . Although it is controversial, some reports have shown the protective effect of estrogen against cataractogenesis (5,6) . Therefore, the decrease in estrogen level with the onset of menopause may increase the risk of cataract in women (5,6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation